2008 46th Annual Allerton Conference on Communication, Control, and Computing 2008
DOI: 10.1109/allerton.2008.4797647
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of correlated sources over a fading multiple access channel

Abstract: Abstract-In this paper we address the problem of transmission of correlated sources over a fading multiple access channel (MAC). We provide sufficient conditions for transmission with given distortions. Next these conditions are specialized to a Gaussian MAC (GMAC). Transmission schemes for discrete and Gaussian sources over a fading GMAC are considered. Various power allocation strategies are also compared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Rajesh and Sharma consider discrete alphabet sources [ 73 ] and the presence of side information over the Gaussian MAC [ 74 ]; they also compare three different joint source-channel coding schemes. The same authors study the Orthogonal MAC in [ 75 , 76 ], and the fading Gaussian MAC in [ 77 ]. Several types of multiuser channels, not necessarily Gaussian, with correlated source side information are studied in [ 78 ], and optimality of separation is proved in those cases for the joint source-channel code, though not yielding the same codes of the source and channel coding problems considered separately.…”
Section: Information Theory Approachesmentioning
confidence: 99%
“…Rajesh and Sharma consider discrete alphabet sources [ 73 ] and the presence of side information over the Gaussian MAC [ 74 ]; they also compare three different joint source-channel coding schemes. The same authors study the Orthogonal MAC in [ 75 , 76 ], and the fading Gaussian MAC in [ 77 ]. Several types of multiuser channels, not necessarily Gaussian, with correlated source side information are studied in [ 78 ], and optimality of separation is proved in those cases for the joint source-channel code, though not yielding the same codes of the source and channel coding problems considered separately.…”
Section: Information Theory Approachesmentioning
confidence: 99%
“…P roof : Fix p(w 1 |u 1 , z 1 ), p(w 2 |u 2 , z 2 ), p(x 1 |w 1 ,ĥ 1 ,ĥ 2 Thus we can use the extended Markov Lemma ( [18]) and hence (u…”
Section: Appendixmentioning
confidence: 99%
“…Joint source channel coding for correlated data on a fading MAC with perfect CSIT and perfect CSIR is studied in [18]. Various power allocation schemes are studied and it is shown that the Random TDMA is suboptimal for transmission of correlated sources.…”
Section: Introduction and Surveymentioning
confidence: 99%
“…However, there arises a problem that if the information sequences are correlated, as in WSN, the SW and MAC regions, referred to as SW-MAC regions, have to intersect for the successful transmission. Even though having an intersection is a sufficient condition [4], it has been widely used in [5], [6] when analyzing the probability of successful transmissions. Reference [5] analyzes the outage probability of a two-correlated-source transmission system over independent block Rayleigh fading channels where both the two sources are aimed to be recovered.…”
Section: Introductionmentioning
confidence: 99%